Con- and Heterospecific Shoaling Makes Invasive Guppies More Risk Taking - Santiago-Arellano, Abigail; Palomera-Hernandez, Vianey; Camacho-Cervantes, Morelia (Frontiers in Ecology and Evolution, 2021)
Invasive species are one of the greatest threats to biodiversity. Behavioral traits are recognized as key to promote individual’s survival in changing conditions. For social species being part of a group is key to carry out vital activities. Heterospecific social environments could provide exotic species with the opportunity to join groups and gain the advantages of being part of a larger population. Short latency to exit a refuge is a behavioral response that could be linked to invasion success as it increases the chances of individuals to locate food sources and other resources in novel environments. The guppy (Poecilia reticulata), a successful invader, has been found to take advantage of the presence of native species to reduce its refuge emergence latency and acquire information. We investigated the effect of heterospecific social contexts that include natives and other invasive viviparous fish on guppies’ refuge emergence latency. We found that guppies’ emergence latency was shorter when accompanied by another guppy than when alone. Their latency was also shorter when with other invaders and when with native goodeids, but with one of the invaders (Pseudoxiphophorus bimaculatus) and with goodeids (Skiffia bilineata) latency reduction was not as high as when with conspecifics or Poecilia gracilis. Our experiment supports both the idea that already established invaders could provide benefits to new ones, and that native species also provide benefits but less than invaders. Increasing our knowledge about conspecific and heterospecific social interactions that could make an exotic species become invasive is key to assess the invasion risk of a community.